Design and Development of an Android-Based Application for Receiving and Tracking Menu Orders in a Café - Rama; Mustamin Tewa; Muhammad Iswal Burhan (Fakultas Teknik Universitas Negeri Makassar, 2026)
This research aims to design and create an Android-based order menu receiving and tracking application for Kopitawa X Empal Gepuk Cafe in Makassar to improve efficiency and accuracy in order management. Application development is carried out using a waterfall approach which consists of five main stages, namely, needs analysis, design, implementation, verification, and maintenance. The technology used includes the Dart programming language with the Flutter framework and Firebase as the database management system. Testing based on the ISO/IEC 25010 standard shows the application has a good level of feasibility. Functional suitability reaches 100%, indicating that all key features are functioning as needed. Optimal performance efficiency with 19% CPU usage and 81 MB of memory. Usability scored 77.9% in the